2015
DOI: 10.1186/s13104-015-1548-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the highly active antiretroviral therapy era on the epidemiology of primary HIV-associated thrombocytopenia

Abstract: BackgroundPrimary HIV-associated thrombocytopenia (PHAT) typically improves with highly active antiretroviral therapy (HAART); however, cases continue to occur. Data comparing the epidemiology of PHAT between the pre-HAART and HAART eras are limited. We retrospectively examined the incidence of PHAT over 28 years in the US Military HIV Natural History Study (NHS) from 1986 to 2013.ResultsSubjects had a nadir platelet count <100 × 109/l with no other identifiable cause. Time periods were categorized as pre-HAAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 14 publications
4
17
1
2
Order By: Relevance
“…Using the target population of PLHIV in the city of Yaounde, women appeared predominant (60.96%), similar to the natural vulnerability to HIV and the epidemiological burden in the general population In this target population of chronically infected Cameroonians, 19.03% of subjects had thrombocytopenia, almost all being mild disorders. Of note, the absence of severe thrombocytopenia can be explained by the fact that most of the patients were monitored within their routine care as outpatient, without emergency and most (79.0%) of them were on treatment against HIV infection, as appropriate ART also contribute in limiting event of thrombocytopenia [14]. The rate of thrombocytopenia slightly differs to reports from Tene et al (13.67% in 2014 within the same city) [9].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Using the target population of PLHIV in the city of Yaounde, women appeared predominant (60.96%), similar to the natural vulnerability to HIV and the epidemiological burden in the general population In this target population of chronically infected Cameroonians, 19.03% of subjects had thrombocytopenia, almost all being mild disorders. Of note, the absence of severe thrombocytopenia can be explained by the fact that most of the patients were monitored within their routine care as outpatient, without emergency and most (79.0%) of them were on treatment against HIV infection, as appropriate ART also contribute in limiting event of thrombocytopenia [14]. The rate of thrombocytopenia slightly differs to reports from Tene et al (13.67% in 2014 within the same city) [9].…”
Section: Discussionmentioning
confidence: 84%
“…in the United States [14]. As also reported by Mbanya et al, in 2002, HIV infection can cause thrombocytopenia by various mechanisms including bone marrow destruction induced by viral activity, ART or immunological factors [15].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Depending on the severity of thrombocytopenia, the most predominant form was mild thrombocytopenia. The absence of severe thrombocytopenia can be explained by the fact that most of the patients followed up in Yaoundé who came for biological monitoring at the CIRCB were not in absolute emergency, and because most (79.0%) of these patients were on treatment .Furthermore it has been shown that an appropriate antiretroviral therapy is the most important step to fight thrombocytopenia [10].…”
Section: Discussionmentioning
confidence: 99%
“…Since the advent of highly active antiretroviral therapy (HAART) introduced in 1996 [1], there has been an increase in the quality and length of life of patients placed on these drugs. The disease condition acquired Immune deficiency Syndrome (AIDS) has gradually evolved into a chronic condition however with subsequent side effects of the drugs and side effects of AIDs itself emerging as the patients live longer.…”
Section: Introductionmentioning
confidence: 99%